Military and political security in the Arctic before and amidst the Ukrainian crisis - I. A. Arzhanov (Lomonosov World Politics Journal, 2024)
In the 21st century, the Arctic has rapidly been transforming from a ‘zone of peace and cooperation’ into an arena of interstate rivalry, where the Russia– NATO confrontation is currently playing a pivotal role. These developments determine the growing interest of both the Russian and foreign academic and expert communities in the problems and prospects for regional security. This paper examines the dynamics of military-political situation in the Arctic within the framework of evolution of the Russia–NATO relations. The first section outlines the key military and political security developments in the Arctic before the Ukrainian crisis. The author emphasizes that already at this stage NATO clearly manifested its desire to limit the Russian presence in the region. In the second section the author offers an original periodization of the Russia–NATO relations in the Arctic after 2014 and in so doing identifies three stages. They are all marked by a gradual yet steady escalation of international tension, manifested in the active efforts undertaken by the NATO member states to remilitarize the region and cultivate a narrative about the Russian threat. This course has been reflected in a whole series of alliance’s military exercises, which, as shown in the article, are becoming increasingly extensive and regular year by year. The author concludes that the Ukrainian crisis has only laid bare the true aspirations of the NATO countries seeking to contain Russia in the Far North and refusing to consider its interests and build a constructive dialogue in the field of military and political security. According to the researcher, this circumstance prevents the normalization of relations between Russia and NATO countries in the years to come.